The post-1991 rural land tenure system in Ethiopia: Scrutinizing the legislative framework in view of land tenure security of peasants and pastoralists - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2019)
Thesis (LLD)--University of Pretoria, 2018.